The Transplantation of Corals as a Coral Reef Conservation in Pandanan Beach, North Lombok - Zakiya Veronika; Tajidan Tajidan (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Naskah ini disusun dari hasil kegiatan MBKM